2015
DOI: 10.1165/rcmb.2014-0231oc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of β-Arrestin-2 and the Mitigation of Established Airway Hyperresponsiveness in a Murine Asthma Model

Abstract: b-Arrestin-2 (barr2) is a ubiquitously expressed cytosolic protein that terminates G protein-coupled receptor signaling and transduces G protein-independent signaling. We previously showed that mice lacking barr2 do not develop an asthma phenotype when sensitized to, and challenged with, allergens. The current study evaluates if an established asthma phenotype can be mitigated by deletion of barr2 using an inducible Cre recombinase. We sensitized and challenged mice to ovalbumin (OVA) and demonstrated that on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Once this was determined, we subjected the mice to the DRA protocol (Figure E) to evaluate whether or not tamoxifen‐induced FoxO1 depletion was associated with changes in the asthmatic phenotype. Tamoxifen treatment had no significant effect on the asthma phenotype in WT mice . Interestingly, we found that loss of FoxO1 by tamoxifen caused an additional decline in total BAL cells and the percentage of eosinophils (from 60.5% to 48.9%) in BAL was reduced in the FoxO1 fl/fl Csf1rcre mice.…”
Section: Resultsmentioning
confidence: 58%
“…Once this was determined, we subjected the mice to the DRA protocol (Figure E) to evaluate whether or not tamoxifen‐induced FoxO1 depletion was associated with changes in the asthmatic phenotype. Tamoxifen treatment had no significant effect on the asthma phenotype in WT mice . Interestingly, we found that loss of FoxO1 by tamoxifen caused an additional decline in total BAL cells and the percentage of eosinophils (from 60.5% to 48.9%) in BAL was reduced in the FoxO1 fl/fl Csf1rcre mice.…”
Section: Resultsmentioning
confidence: 58%
“…21 β-arrestin2 flox/flox mice were generated by flanking exon 2 of the mouse β-arrestin2 gene ( Arrb2 ) with LoxP sites 21 and subsequent backcrossing into a C57/B6 genetic background for 7 generations. Conditional cardiomyocyte deletion of β-arrestin2 was generated by crossing β-arrestin2 flox/flox mice with transgenic mice expressing a tamoxifen-inducible Mer-Cre-Mer recombinase under the control of the α-myosin heavy chain promoter, 22 (Jackson lab, stock #005650) to generate β-arrestin2 flox/+ /αMHC MerCreMer mice and then crossed with β-arrestin2 flox/flox to yield the genotypes used in the study (Figure S3).…”
Section: Methodsmentioning
confidence: 99%
“…For example, barrestin-2 null mice show an attenuated asthma-like phenotype (14), and, as shown by a recent study, where barrestin-2 was deleted after the asthma-like phenotype had been established, barrestin-2 is essential for perpetuation of AHR (15). Furthermore, we have recently identified that certain "b-blockers" (such as carvedilol) that lack agonism toward the Gas signaling pathway, yet activate ERK1/2 in cell-based assays, restore the asthma-like phenotype in PNMT-KO mice, and are ineffective at attenuating the phenotype in wild-type (WT) mice (16).…”
mentioning
confidence: 74%